Pengaruh Model Jigsaw Terintegrasi Pembelajaran Berdiferensiasi Terhadap Keterampilan Kolaborasi Dalam Pembelajaran IPAS - Eryva Tri Anggraini; Idam Ragil Widianto Atmojo (Universitas Sebelas Maret, 2025)
The 21st century demands students to have various important skills, one of which is collaboration skills which are very relevant to be developed since elementary school level. This study aims to determine the effect of the Jigsaw learning model integrated with a differentiated learning approach on students' collaboration skills in science learning in grade IV of elementary school. Two groups are used in this study, which employs a quantitative approach and a quasi experimental methodology. The experimental class uses the Jigsaw model in conjunction with differentiated learning, while the control class uses traditional learning. Productivity, active engagement, effective communication, responsibility, and cooperation are the five variables that make up the study instrument, which also includes a collaboration skills observation sheet and a learning style questionnaire. The independent sample t-test findings revealed a significance value of 0.002 (<0.05), indicating a significant difference between the experimental and control groups. The experimental class showed a more significant increase in collaboration skills, indicated by an increase in the number of students with a very good score category on the posttest (91–100) of 7 students, compared to only 1 student in the control class. In addition, the visual learning style is the most dominant in the experimental class, supporting the success of the implementation of content differentiation and the learning process. The integration of the Jigsaw model and differentiated learning has been proven to create a collaborative learning environment that adapts to the needs and characteristics of students, thereby encouraging active involvement and improving collaboration skills.